Sistema para el Control de Proyectos del MIES del Cantón Las Naves - Guaman Estrada, Juan Gabriel (2018)
The use of software in a company or institution, whether public or private, allows it to improve its performance, since there are many advantages such as: the margin of error that could exist is very minute since an application fully complies with each of the processes for which it was programmed, in addition the response time is short compared to what a human could take in giving the same answer therefore it makes the use of an application in a company very feasible. However, in the association of disabled people first of May in the city of Las Naves, there are inconveniences with the handling of the information that this institution has, since it is very extensive, allowing problems such as: delay in the response time to be presented. users, incomplete projects and loss of information one of the most important inconveniences produced in the institution is that there are incomplete projects, because it was not done in the agreed time of this operation, the resource is lost or the project is not executed as example we can mention, there is a capital of a foreign institution linked to the association for delivery of special equipment for disabled people the time the project is executed is 1 year because there is no control for projects is not used for everything the captain provided by the institution then the surplus money returns to the institution that offered it, assuming that not all Disabled people benefit since there was control over the time of execution of the project and it did not come to be fulfilled in its entirety, losing important resources for the institution and its users, that is why it is intended to make use of the technology that currently exists and cover all these drawbacks.